Herpes simplex virus type 2: a key role in HIV incidence - Glynn, Judith R.; Biraro, Samuel; Weiss, Helen A. (Aids, 2009)
Many epidemiological studies have found a strong association between HSV-2 infection and HIV infection, including longitudinal studies in which it was known that the HSV-2 infection preceded the HIV infection [1]. However, two recent trials of suppressive therapy of HSV-2 with acyclovir (400 mg b.i.d) showed no reduction in HIV incidence [2,3]. Although this may simply reflect the difficulty of adequately suppressing HSV-2 reactivations with the drug regimen used, the results have led some to challenge the importance of HSV-2 infection as a risk factor for HIV [4]. In this issue, Tobian et al.[5] use data from the Rakai male circumcision trial to assess the effect of prevalent and incident HSV-2 infection on HIV incidence. They found that prevalent HSV-2 infection increased HIV incidence three-fold, and that men who acquired HSV-2 during follow-up had a six-fold risk of HIV incidence, in analyses adjusted for sexual behaviour. These results are very similar to those found in a systematic review [1]. This included cohort and nested case–control studies up to 2004, and identified 18 that were adjusted for age and sexual behaviour. We have re-run the meta-analysis including more recent studies that fit the same criteria (Fig. 1). Six additional studies, as well as that by Tobian et al.[5], are included: one in men from the circumcision trial in South Africa [6]; two in women in the general population, in Uganda and Zimbabwe [7]; two in female sex workers in Kenya [8] and Tanzania [9]; and one in men who have sex with men (MSM) in the US [10]. Summary estimates of the relative risk (RR) show a strong and consistent association of prevalent HSV-2 and incident HIV after adjusting for age and measures of sexual behaviour [RRwomen = 3.4, 95% confidence interval (CI) 2.4–4.8; RRmen = 2.8, 2.1–3.7; RRsex workers = 1.5, 0.75–3.0; RRMSM = 1.6, 1.2–2.0). In addition, a cohort study in Uganda found an adjusted rate ratio of 8.7 (1.1–67.2) for men and women combined
Keywords: herpes simplex virus type 2, HIV, incidence